Website Technology Trends for Augmented Reality Development - Rakhmi Khalida; Siti Setiawati (Universitas Ahmad Dahlan, 2020)
Augmented reality (AR) is a technology that is gaining increasing attention from academics and industry. AR is relied upon to be an innovative technology to enrich ways of interacting with the physical and cyberspace around users that can enhance user experience in various fields. Platforms for AR applications are usually hardware based and mobile based, for mobile applications AR is usually based. AR-based hardware requires quite expensive support, this is seen from the rendering space requirements and this makes it inflexible while AR-based applications on mobile smartphones require large storage space and do not make it convenient for cross-platform use. Currently many researchers are trying to create and develop website-based AR, as a solution to the spread of AR to be flexible and save storage space, website technology development trends are used as a method for improving the performance of website-based AR. Other support comes from open-source software and more developer platforms and program courses for Web AR that are made public. This paper reviews the state-of-the-art, various methods, technologies and challenges of existing AR, this can be a trigger for more research interest and efforts to provide AR experience